Sampled Reference Frame Algorithm Based on Space Vector Pulse Width Modulation for Five Level Cascaded H-Bridge Inverter - Gomathi C; Navya Nagath; Veerakumar S (Institute of Advanced Engineering and Science, 2014)
In This paper the Sampled Reference Frame Algorithm for Five Level Cascaded H-Bridge Inverter is presented. This simple method is less computation method than Sector Identification. This SVPWM can drive any Multilevel Inverter with good DC utilization, less switching stress. This is used for high voltage and high power applications. By using Sampled Reference Frame Algorithm, there is no use of look up tables, sector selection, no need of reference voltage and angle information, 3φ to 2φ transformation. The inverter’s structure of these inverters is developed by using MATLAB SIMULINK software.